Breaking the fourth wall and (meta)fictional reference - Semeijn, Merel (Proceedings of the Amsterdam Colloquium, 2025)
I investigate statements in fiction that ‘break the fourth wall’ (i.e., statements through which a fictional character somehow acknowledges the fictionality of their world) and suggest that they are a mirror image of ‘parafictional statements’, i.e., statements about what is true in some fiction. I explore two possible analyses, according to which statements that break the fourth wall are either a type of fictional statement or are a type of metafictional statement, and propose a synthesis of these two analyses.